Smart Materials Enabled with Artificial Intelligence for Healthcare Wearables. (12th August 2021) - Zheng, Youbin; Tang, Ning; Omar, Rawan; Hu, Zhipeng; Duong, Tuan; Wang, Jing; Wu, Weiwei; Haick, Hossam
Abstract: Contemporary medicine suffers from many shortcomings in terms of successful disease diagnosis and treatment, both of which rely on detection capacity and timing. The lack of effective, reliable, and affordable detection and real‐time monitoring limits the affordability of timely diagnosis and treatment. A new frontier that overcomes these challenges relies on smart health monitoring systems that combine wearable sensors and an analytical modulus. This review presents the latest advances in smart materials for the development of multifunctional wearable sensors while providing a bird's eye‐view of their characteristics, functions, and applications. The review also presents the state‐of‐the‐art on wearables fitted with artificial intelligence (AI) and support systems for clinical decision in early detection and accurate diagnosis of disorders. The ongoing challenges and future prospects for providing personal healthcare with AI‐assisted support systems relating to clinical decisions are presented and discussed. Abstract : Smart materials‐based artificial intelligence (AI)‐assisted healthcare wearable devices are revolutionizing the healthcare field. This review summarizes the recent advances in smart materials and their applications in healthcare wearables. The aspects of biosensing materials, wearable substrate materials, innovative wearable sensors for health monitoring and AI‐assisted data processing and healthcare decision‐making are highlighted.